Survival outcomes of beta-blocker usage in HER2-positive advanced breast cancer patients: a retrospective cohort study - Hui-Hsia Hsieh; Tien-Yuan Wu; Chi-Hua Chen; Yu-Hung Kuo; Mann-Jen Hour (SAGE Publishing, 2023)
Background: Clinical trials investigating the effects of beta-blockers (BBs) on cancer are underway. Evidence from preclinical research suggests that BBs could serve as anticancer agents and immune boosters. There is conflicting evidence regarding the effect of BB use on clinical outcomes in patients with breast cancer. Objectives: The study aimed to determine whether BB use is associated with progression-free survival (PFS) and overall survival (OS) in patients receiving anti-human epidermal growth factor receptor 2 (HER2) treatment for advanced breast cancer. Design: Retrospective hospital-based study. Methods: The participants enrolled were breast cancer patients with advanced HER2-positive status who initiated trastuzumab monotherapy or concomitant therapy with trastuzumab and any dose of BB. The patients were enrolled between January 2012 and May 2021 and divided into three groups based on whether they received a BB or not in the therapeutic regimen: BB−/trastuzumab+, BB+ (non-selective)/trastuzumab+, and BB+ (selective)/trastuzumab+. PFS and OS were the primary and secondary endpoints, respectively. Results: The estimated median PFS in the BB−/trastuzumab+, BB+ (non-selective)/trastuzumab+, and BB+ (selective)/trastuzumab+ groups was 51.93, 21.50, and 20.77 months, respectively. The corresponding OS was 56.70, 29.10, and 27.17 months. The intergroup differences in these durations were significant. Both PFS [adjusted hazard ratio (HR): 2.21, 95% confidence interval (CI): 1.56-3.12; p  < 0.001]) and OS (adjusted HR: 2.46, 95% CI: 1.69-3.57; p  < 0.001) were worse when BBs were used. Conclusion: Our study provides important evidence that BB use potentially has a negative effect on patients with HER2-positive advanced breast cancer. Nevertheless, despite the study's results, cardiovascular disease (CVD) should be appropriately treated in patients with HER2-positive advanced breast cancer. Other types of drugs can be used to treat CVD, but BB use should be avoided. Large real-world database and prospective studies should be conducted to validate the results of this study.